Pengetahuan Keluarga Tentang Mobilisasi Klien Pasca Stroke di Rumah Berhubungan Dengan Kemampuan Pemenuhan Kebutuhan Mobilisasi di Kelurahan Sadangserang Wilayah Kerja Puskesmas Puter Kota Bandung - Indrio David Pratama Putra; Kuslan Sunandar; Tati Suheti (Jurnal Medika Cendikia, 2018)
Stroke or cerebrovascular injury (CVA) is the loss of brain function caused by the cessation of blood supply gets brain (Bruner & Sudarth, 2002). In stroke there is one disability that is interference mobilization. Conduct disorders mobilization should be assisted by the family, where family members must have knowledge of the client's ability to mobilize the needs of stroke. In addition to having knowledge of the family meet the needs of mobilization, the family must also be able to take action mobilization stroke clients at home. This study aims to determine the family relationships of knowledge about the mobilization of stroke clients at home with the capability needs of mobilization in Puskesmas Puter Sadangserang. Cross-sectional design with a sample of 46 people. Techniques used in data collection questionnaire to collect data using a checklist of knowledge and observation to collect data on the ability of families in the capability needs of stroke clients mobilization at home. There was significant correlation between family knowledge about the mobilization of clients home with the ability of mobilization requirements. Puskesmas Puter Sadangserang with p-value of 0.001 <α (0.05). Suggestions for Puskesmas for frequen home visits to families who have a stroke client and trainning the family in caring for stroke clients at home.